2022
DOI: 10.3389/fbioe.2022.1076320
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal in vivo biodistribution of nano and micro sized hydroxyapatite particles implanted in a bone defect

Abstract: Hydroxyapatite (HA) has been widely used as a bone substitute and more recently as a carrier for local delivery of bone targeted drugs. Majority of the approved HA based biomaterials and drug carriers comprise of micrometer sized particulate HA (mHA) or granules and can therefore only be used for extracellular drug release. This shortcoming could be overcome with the use of cell penetrating HA nanoparticles (nHA) but a major concern with the clinical use of nHA is the lack of data on its in vivo biodistributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…Blood levels of bone biomarkers were not affected by local ZA application compared to the corresponding systemic ZA application group. A recent study of our team further confirmed this conclusion [ 43 ]. By loading 14 C-ZA into a micro- or nano-HA biomaterial, it was found that more than 99 % of 14 C ZA still was locally retained within the defect and less than 0.1 % of the ZA could be detected in other organs, regardless of particle size, after 4 weeks in a rat tibial defect model.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Blood levels of bone biomarkers were not affected by local ZA application compared to the corresponding systemic ZA application group. A recent study of our team further confirmed this conclusion [ 43 ]. By loading 14 C-ZA into a micro- or nano-HA biomaterial, it was found that more than 99 % of 14 C ZA still was locally retained within the defect and less than 0.1 % of the ZA could be detected in other organs, regardless of particle size, after 4 weeks in a rat tibial defect model.…”
Section: Discussionsupporting
confidence: 76%
“…By loading 14 C-ZA into a micro- or nano-HA biomaterial, it was found that more than 99 % of 14 C ZA still was locally retained within the defect and less than 0.1 % of the ZA could be detected in other organs, regardless of particle size, after 4 weeks in a rat tibial defect model. ZA is tightly linked and chemically bound to the HA phase in a biphasic scaffold [ 15 , 43 ]. The targeted high biological effect of ZA significantly reduced the degradation of CaS/HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioceramics can be synthesized from a range of materials, including alumina, zirconia, magnesia, carbon, silica-based compounds, calcium-based compounds, and various other chemicals . The initial development of bioceramics aimed to serve as bone substitutes for implantation for its superior biocompatibility, high mechanical strength, and corrosion resistance. , In recent years, through optimization of the material, processing methods, and physicochemical properties of bioceramics, the application of bioceramic scaffolds has expanded beyond bone regeneration to the integrated regeneration of OC tissue . For endogenous OC tissue engineering, bioceramic scaffolds can be functionalized to regulate stem cell functions, thus promoting AC and bone regeneration .…”
Section: Scaffolds For Ac and Oc Endogenous Tissue Engineeringmentioning
confidence: 99%
“…Ceramic materials have proven successful in addressing bone tissue defects, falling under the umbrella of bioceramics. Bioceramics encompass inorganic, non-metallic materials with biocompatibility, high melting points, electrical resistance, and corrosion resistance 11 . While ceramic scaffolds offer promise for various applications in oral and maxillofacial surgery, periodontal treatments, and orthopedics, their brittle nature restricts their use to non-load-bearing applications 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%